(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background – Children with urolithiasis (UL) are often encountered in general pediatric practice. Its rising incidence, high recurrence rate, serious long term consequences paucity of data on pediatric urolithiasis led to present research work. Recurrence usually remains unaltered unless dietary restrictions are followed stringently so emphasis in present research was on analysis of diet consumed by participants.Material Methods – Children with UL were enrolled from general pediatrics OPD of an urban hospital over 22 months in a prospective study. Data was collected on clinical profile, 24 hour dietary details, blood urine investigations and USG abdomen. Attempts were made to get basic metabolic work-up in as many children as possible.Results – Abdominal pain alone or with symptoms of UTI was found in 83.3 45.8 subjects. Important etiological associations found were UTI(62.7),positive family history of UL (45.8) and obesity (10.4). Idiopathic hypercalciuria, hyperuricosuria hyperoxaluria were found in 9 (18.7),2(4.2) 12(25) participants. Daily intake of liquids calcium was low in 79 72.9 children respectively. Intake of both salt proteins was high in 62.5 children. Persistence of symptoms found in 58.3 subjects. Recurrence was found in 14.5 subjects.Conclusion – Having high index of suspicion of UL in all children presenting with recurrent unexplained UTI or recurrent abdominal pain and advocating USG abdomen early in such children can aid in timely diagnosis of UL. Simple dietary manipulations like adequate daily fluid calcium intake along with avoiding high salt animal protein diet may be beneficial by decreasing the recurrence rate of UL.